Resin infiltration as a minimally invasive treatment for incipient dental caries lesions - Alain Manuel Chaple Gil; Mariana Alea González (Editorial Ciencias Médicas, 2017)
Minimal intervention in cariology has been defined as the philosophy of dental care that deals with the treatment of the first occurrence, early detection and treatment of dental caries. Resin infiltration is one of the techniques used for early treatment and arrest of incipient lesions. The objective is to show the usefulness of fluid resins for infiltration of a first and second lower permanent molar with an incipient dental caries lesion. A 17 year-old male patient with a healthy history attended dental consultation with dark brown point spots on the lower left hemiarch near the central pit and on the vestibular groove of 36 and 37, respectively, of not more than 1 mm in depth. Incipient dental caries lesions were diagnosed and it was decided to perform infiltration of low viscosity composite or fluid resin in a single visit. Use of fluid composite resins is suitable for infiltration of incipient enamel caries lesions, for it prevents spread and seals the gaps in the affected enamel. It is a minimal intervention technique in cariology providing immediate solution to these processes as well as greater ease to solve dental caries disease balancing esthetic expectations with expectations related to the maintenance of healthy dental structures.